Renal Tumours : Risk Factors, Clinical Profile, and Histopronosis : A Review of 58 Cases - alafifi, mahmoud; Elkebir, Asmaa (Jour Med Resh and Health Sci, 2022)
INTRODUCTION Kidney cancer accounts for 3% of all adult solid cancers, with clinical and imaging findings evoking a diagnosis that is confirmed by histology, and a clinical and historical prognosis. The goal of this study is to describe the risk factors for kidney cancer as well as the prognostic profile. PATIENTS AND METHODS: The UHC ibn Rochd’s Urology andrology department conducted a descriptive study with retrospective data collection from February 2018 to June 2021. Patients who had a total nephrectomy for a renal tumour were included in this study. Patient age, sex, clinical and paraclinical data, and anatomopathological results were all collected on pre-determined forms. RESULTS: The mean age was 62.8 years. The M/F ratio was 1.9 (male predominance). The mean time to consultation was 8 months (1 month). The risk factors were mainly smoking (21%), obesity (7%) and hypertension (10.3%). 38% of cases were diagnosed with low back pain, followed by haematuria in 24%. The discovery was incidental in 11% of cases. ECOG /OMS rated 1 in 55.1%, 2 in 31%. Left nephrectomy was the most common in 62% of cases.90% of cases were renal cell carcinoma (RCC).3% of cases were renal metastases.95% were clear RCC.10% of cases had a sarcomatoid component.PT2 stage was predominant (47.8%) followed by PT3 (34.5%). PT4 stage: 10.35%. In 6.9% of cases, lymph node metastases were found, with Furhman grade II predominating (51.7%) followed by grade IV (19%). Vascular emboli: 17% of cases. CONCLUSION: Kidney cancer is a clear cell renal cell carcinoma ccRCC until proven otherwise; two men are affected for every one woman. In half of the cases, the prognosis is intermediate. The risk factors that must be addressed are smoking and hypertension.